Review of Chapter 8, “The Orthodox World and Christian-Jewish Dialogue.” Karma Ben-Johanan’s "Jacob’s Younger Brother: Christian-Jewish Relations after Vatican II" - Langer, Ruth (Studies in Christian-Jewish Relations, 2023)
No abstract is available.